Prospective study of erythropoietin use on quality of life and cost effectiveness in acute myeloid leukemia and allogeneic hematopoietic stem cell transplantation patients. Issue 1 (28th June 2012) - Michallet, Mauricette; Goldet, Karine; Sobh, Mohamad; Morisset, Stéphane; Chelghoum, Youcef; Thomas, Xavier; Barraco, Fiorenza; Ducastelle, Sophie; Labussière, Hélène; Renzullo, Catherine; Paillet, Carole; Pivot, Christine; et al.
Abstract BACKGROUND: Despite frequent anemia and multiple transfusions in patients undergoing chemotherapy and allogeneic hematopoietic stem cell transplantation (allo‐HSCT) for acute myeloid leukemia, recommendations for use of erythropoiesis‐stimulating agents (ESAs) in these populations are still missing. The primary objective was the effect of ESA administration on patient's quality of life (QoL). Secondary objectives were hemoglobin (Hb) recovery, red blood cell (RBC) transfusions, overall survival, and event‐free survival. METHODS: Adult patients with Hb ≤ 11 g/dL after consolidation chemotherapy for acute myeloid leukemia (group 1), or after allo‐HSCT for any hematological diseases (group 2), were prospectively included. ESA was administered subcutaneously once per week during a maximum period of 6 months and was stopped when Hb level reached 12 g/dL. A paired‐matched analysis using a historical control group was performed for secondary endpoints. Fifty‐two patients were included in group 1, and 55 patients were in group 2. RESULTS: For the global population, a significant improvement of QoL was noticed with ESA use; 83% (group 1) and 71% (group 2) of patients achieved an Hb level ≥ 12 g/dL without transfusion requirement. The pair‐matched analysis showed a reduction of 4 RBC units per patient in group 1 (P = .0002) and 3 RBC units per patient in group 2 (P = .04). No significant difference in terms of thromboembolic events, overall survival, and event‐free survival was observed between ESA and control groups. A RBC transfusion median savings of €1712 per patient was estimated in each group. CONCLUSIONS: ESAs have a clinical and economic benefit on Hb recovery, could improve a patient's QoL, and lead to a significant reduction in number of RBC transfusions with no effect on survival. Cancer 2013. © 2012 American Cancer Society.